Circadian Clock Regulates Inflammation and the Development of Neurodegeneration - Wang, Xiao-Lan; Li, Lianjian (Frontiers in Cellular and Infection Microbiology, 2021)
The circadian clock regulates numerous key physiological processes and maintains cellular, tissue, and systemic homeostasis. Disruption of circadian clock machinery influences key activities involved in immune response and brain function. Moreover, Immune activation has been closely linked to neurodegeneration. Here, we review the molecular clock machinery and the diurnal variation of immune activity. We summarize the circadian control of immunity in both central and peripheral immune cells, as well as the circadian regulation of brain cells that are implicated in neurodegeneration. We explore the important role of systemic inflammation on neurodegeneration. The circadian clock modulates cellular metabolism, which could be a mechanism underlying circadian control. We also discuss the circadian interventions implicated in inflammation and neurodegeneration. Targeting circadian clocks could be a potential strategy for the prevention and treatment of inflammation and neurodegenerative diseases.